Strategy To Increase Children's Interest In Reading Through a Program Gelar Baca Using The Read Aloud Method: Strategi meningkatkan minat baca pada anak melalui program gelar baca dengan metode read aloud - Indah Juliyanti; Ira Wikartika (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The reading degree program is an ruang belajar aqil initiative which aims to increase reading interest and literacy skills of elementary school students in the education 4.0 era. This research shows that interest in reading among elementary school children is still low, so then it is need to be handled. The program implementation study includes four main stages: observation and problem mapping, planning, implementation, and evaluation. The methods used include read aloud activities for grades 1-2 and reading degrees for grades 3-6. The research results show that this program is effective in increasing students' reading interest and understanding of the information they read. Technology integration through digital platforms such as the ruang belajar aqil website expands the reach of the program and provides access to various reading sources. In conclusion, the reading degree program has succeeded in being a significant step in improving literacy skills and encouraging interest in reading among elementary school students, with the potential for further development through the use of digital technology.